2006
DOI: 10.1016/j.jelechem.2006.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Ion distributions at the nitrobenzene–water interface electrified by a common ion

Abstract: Synchrotron X-ray reflectivity is used to study ion distributions at the liquid-liquid interface between a nitrobenzene solution of tetrabutylammonium tetraphenylborate (TBATPB) and a water solution of tetrabutylammonium bromide (TBABr). The concentration of TBABr is varied to alter the ion distribution. Our X-ray measurements are inconsistent with several commonly used theories of ion distributions, including Gouy-Chapman, modified Verwey-Niessen, and the MPB5 version of the Poisson-Boltzmann equation. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 85 publications
(169 reference statements)
5
73
0
Order By: Relevance
“…It has been found that while the mean-field Poisson-Boltzmann framework provides a generally good description for the ion profiles that matches well with experimental results obtained by x-ray structural measurements, the linearized Guoy-Chapman approximation is insufficient for most general cases (24). For completeness, we will now illustrate the solution to the Poisson-Boltzmann equation for the case when the membrane across the two dielectric media is charged (polarizable), including the particular interesting case of the neutral (non-polarizable) interface.…”
Section: Case Study Definedsupporting
confidence: 59%
“…It has been found that while the mean-field Poisson-Boltzmann framework provides a generally good description for the ion profiles that matches well with experimental results obtained by x-ray structural measurements, the linearized Guoy-Chapman approximation is insufficient for most general cases (24). For completeness, we will now illustrate the solution to the Poisson-Boltzmann equation for the case when the membrane across the two dielectric media is charged (polarizable), including the particular interesting case of the neutral (non-polarizable) interface.…”
Section: Case Study Definedsupporting
confidence: 59%
“…As a result of the higher relative permittivity of nitrobenzene (e r = 34.8) and the lower range of electric potential (jΔϕ max j = 0:277 V), the correlation coupling strength in those experiments was small (Γ ≈ 0.7), and it was shown that the effect of correlations was negligible (13). However, the reflectivity data in Fig.…”
Section: Discussionmentioning
confidence: 86%
“…This theory predicts the ion number density profiles nðzÞ, which are then used to calculate electron density profiles ρðzÞ (12,13). X-ray reflectivity is determined from ρðzÞ by use of the Parratt algorithm (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Schlossman and coworkers [184][185][186][187] have used synchrotron X-ray reflectivity to study ion distribution at the liquid|liquid interface between a nitrobenzene solution of tetrabutylammonium tetraphenylborate and a water solution of tetrabutylammonium bromide. These structural measurements are well described by the ion distributions predicted by a version of the Poisson-Boltzmann equation that explicitly includes a free energy profile for ion transfer across the interface.…”
Section: Other Techniquesmentioning
confidence: 99%